CLASSIFICATION FEATURES OF INTERNATIONAL PARLIAMENTARY INSTITUTIONS: TO THE QUESTION OF THE THEORETICAL ASPECTS OF INTERNATIONAL PARLIAMENTARISM - ДУДКО, Ірина (Київський національний університет імені Тараса Шевченка, 2023)
B a c k g r o u n d . The search for new forms and directions of activity of the Verkhovna Rada of Ukraine in the international arena actualizes the need for theoretical understanding of the classification features of international parliamentary institutions as a problem that has not found coverage in domestic science today. At the same time, the theoretical aspects of the formation and functioning of the structures of international parliamentarism are actively studied by foreign authors, which makes it possible to generalize existing developments and form a holistic view of the specifics of international parliamentary institutions. The object of research is the classification features of international parliamentary institutions that form a multilevel and multivariate system of modern international parliamentarism. M e t h o d s . The paper uses a descriptive method focused on analytical description and allocation of separate groups of international parliamentary institutions; systemic method – to identify internal organizational principles and specifics of the functioning of international parliamentary institutions; empirical method – to highlight the practical and political potential of international parliamentary structures. R e s u l t s . The article is focused on consideration of organizational bases and principles of functioning of international parliamentary institutions of different levels with identification of their formal status and political opportunities. It has been formed objective ideas about the potential of international parliamentary institutions in the international arena as a platform for realization of urgent international problems of supranational, regional or special political orientation. The system of interrelations of international parliamentary institutions with related international organizations with the tendency of turnover of their status and powers in accordance with international structures has been determined. The prospects of scientific research in the direction of international parliamentary institutions as a potential resource in the system of international diplomacy and international relations of Ukraine are outlined. C o n c l u s i o n s . The practical aspect of interaction with international parliamentary institutions implies a clear awareness of their formal status, organizational principles, political capabilities, which makes possible a more specific, and thus effective course of the Verkhovna Rada of Ukraine in the field of interparliamentary diplomacy and inter-parliamentary relations.

В с т у п . Актуальність і мета дослідження. Пошук нових форм і напрямів діяльності Верховної Ради України на міжнародній арені актуалізує потребу теоретичного осмислення класифікаційних ознак міжнародних парламентських інституцій як проблеми, що не знайшла на сьогодні висвітлення у вітчизняній науці. Водночас теоретичні аспекти формування і функціонування структур міжнародного парламентаризму активно досліджуються закордонними авторами, що уможливлює узагальнення наявних напрацювань та формування цілісного уявлення про специфіку міжнародних парламентських інституцій. Об'єктом дослідження є класифікаційні ознаки міжнародних парламентських інституцій, що формують багаторівневу і багатоваріативну систему сучасного міжнародного парламентаризму. М е т о д и . Використано дескриптивний метод, орієнтований на аналітичне описання і виокремлення окремих груп міжнародних парламентських інституцій; системний – з метою виявлення внутрішніх організаційних засад і специфіки функціонування міжнародних парламентських інституцій; емпіричний – для висвітлення практико-політичного потенціалу міжнародних парламентських структур. Р е з у л ь т а т и . Орієнтовано на розгляд організаційних засад та принципів функціонування міжнародних парламентських інституцій різного рівня з виявленням їхнього формального статусу й політичних можливостей. Сформовано об'єктивні уявлення про потенціал міжнародних парламентських інституцій на міжнародній арені як платформи реалізації актуальних міжнародних проблем наднаціонального, регіонального або спеціального політичного спрямування. Визначено систему взаємозв'язків міжнародних парламентських інституцій зі спорідненими міжнародними організаціями із тенденцією змінюваності їхнього статусу та повноважень відповідно до міжнародних структур. Окреслено перспективи наукових пошуків у напрямі міжнародних парламентських інституцій як потенційного ресурсу в системі міжнародної дипломатії і міжнародних відносин України. В и с н о в к и . Визначено, що практичний аспект взаємодії з міжнародними парламентськими інституціями передбачає чітке усвідомлення їхнього формального статусу, організаційних засад, політичних можливостей, що уможливлює більш конкретизований, а за цим – і ефективний курс Верховної Ради України у сфері міжпарламентської дипломатії і міжпарламентських відносин.
КЛАСИФІКАЦІЙНІ ОЗНАКИ МІЖНАРОДНИХ ПАРЛАМЕНТСЬКИХ ІНСТИТУЦІЙ: ДО ПИТАННЯ ПРО ТЕОРЕТИЧНІ АСПЕКТИ МІЖНАРОДНОГО ПАРЛАМЕНТАРИЗМУ
Keywords: international parliamentarism; international parliamentary institutions; classification features; potential of international parliamentarism.; міжнародний парламентаризм; міжнародні парламентські інституції; класифікаційні ознаки; потенціал міжнародного парламентаризму.